Oral Glucose Tolerance Test by Pure Glucose Vs. Sucrose to Diagnose a ‘‘Mild’’ Early Reactive Hypoglycemia. A Case Report: L’hyperglycémie provoquée par voie orale au glucose pur vs au saccharose pour diagnostiquer une hypoglycémie réactionnelle précoce ‘fruste’ : à propos d’un cas - Lendoye, Elisabeth; Nsame, Daniela; N’negue ep. Mezui-Mbeng, Marie-Andrée; Moukambi, Lydie; Leboueny, Marielle; Ngoma, Laury; Agnenguilet, Anaïs; Ngoungou, Edgard Brice; Djoba Siawaya, Joël Fleury (HEALTH SCIENCES AND DISEASE, 2022)
ABSTRACT We report the results of glycemic indexes and several oral glucose tolerance test with pure glucose (OGTTGlc) vs. sucrose (OGTTSucr). In October 2021, all of the patient's blood glucose levels were normal. During OGTTGlc: T1HGlc < T0Glc or during OGTTSucr: T1HSucr > T0Sucr. In January 2022, blood glucose levels were still normal, Insulin resistance was occurring (HOMA-IRoct = 2.20 vs HOMA-IRjan = 3.68) and Insulin sensitivity was gradually collapsed. This allowed us to diagnose a 'mild' early reactive hypoglycemia. OGTT remains the best means for a clinical exploration of glucose metabolism disorders. RÉSUMÉ Nous rapportons les résultats d’indices glycémiques et de plusieurs hyperglycémies provoquées par voie orale au glucose pur (HGPOglc) et saccharose (HGPOSacc). En octobre 2021, toutes les glycémies de la patiente étaient normales. Pendant l’HGPOglc : T1HGlc < T0Glc or durant l’HGPOSacc : T1HSacc > T0Sacc. En janvier 2022, les glycémies étaient toujours normales, l’insulinorésistance apparaissait (HOMA-IRoct = 2,20 vs HOMA-IRjan = 3,68) et l’insulinosensibilité s’effondrait progressivement. Ceci nous a permis de poser le diagnostic d’hypoglycémie réactionnelle précoce ‘fruste’. L’HGPO demeure l’examen de choix pour l’exploration clinique des troubles du métabolisme du glucose.